The Biodiversity of Edible Flowers: Discovering New Tastes and New Health Benefits - Benvenuti, Stefano; Mazzoncini, Marco (Frontiers in Plant Science, 2021)
Floriculture and horticulture have always been two parallel and very distinct agronomic realities. Floriculture is concerned with meeting the ornamental needs of our urban ecosystems, while horticulture is based on meeting food requirements. These two activities have now converged toward a food chain where flowers are conceived of as a sort of “new vegetable” and one of the most promising novelties to satisfy the growing need for food innovation both in terms of an organoleptic and nutraceutical profile. This novelty has rapidly evolved, especially following the growing scientific evidence of the human health benefits of flowers used as food. The typically high pigment concentration of the corollas (especially flavonoids and carotenoids), which have evolved to chromatically attract pollinators, indicates a marked nutraceutical activity especially in terms of antioxidant power. In this review, we first attempted to explore which species are most promising and which should be avoided due to real or suspected toxicity problems. The nutraceutical virtues were therefore highlighted trying to focus attention on those “functional phytochemicals” capable of counteracting some specific human pathologies. Furthermore, the organoleptic profile of edible flowers was investigated since this is one of the least known aspects. The cropping systems suitable for their cultivation were therefore hypothesized and finally the criticalities of edible flowers were addressed in terms of shelf life and marketing opportunities.